IMPROVEMENT OF STUDENTS' CRITICAL THINKING SKILLS AS AN IMPACT OF THE APPLICATION OF THINK TALK WRITE ON EARTH AND SOLAR SYSTEM - Nufus, Fitrotin; Hartiningsih, Try; Ahied, Mochammad; Wahyuni, Eva Ari; Putera, Dwi Bagus Rendy Astid (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
This research aimed to determine whether the Think Talk Write model increased students' critical thinking skills regarding the earth and solar system. A quasi-experimental research design was used, specifically Nonequivalent Control Group Design. The study was conducted at Al-Kholiliyah Bangkalan Middle School during the 2023/2024 academic year, involving all class VII students. The VII-A cohort served as the experimental class, where the Think Talk Write model was implemented, while the VII-B cohort served as the control class, where direct instructional method was used. Purposive sampling was employed to select the sample groups. The N-Gain Score test was utilised to analyze the improvement in critical thinking skills. The results show a significant increase in critical thinking skills among students in the experimental class, with 100% achieving an improvement categorized as medium. In contrast, the control class showed only 7.14% improvement in medium category, with 85.71% of students falling into the low improvement category.